Effects of Honey Sales Performed via Television Commercials on Consumers’ Buying Behavior - Kabakcı, Dilek; Çankaya, Soner; Akdeniz, Gökhan; Derebaşı, Engin (My University, 2020)
Honey is the most known and consumed bee product by consumers. Therefore, from the past to thepresent, the investigation of the factors affecting the supply and consumption of honey has been onthe agenda of the researchers. For this purpose, in our survey study, the effects of honey sales carriedout via television channels (commercials) on consumers were investigated. According to the surveyresults, it was determined that 87.91% of consumers had a negative view about honey sales performedvia television, 3.54% had a positive opinion, and 8.55% had no opinion on the issue. It was foundthat 5.83% of consumers bought honey through television commercials, and the education, income,gender and number of individuals in their households have an effect on the tendency to buy honey.Regarding the exposing of companies selling fake or adulterated honey by the Ministry of Agricultureand Forestry, results showed that this situation positively affected 54.53 of consumers in terms oftrust in honey positively, affected 13.30% of consumers negatively, and did not affect 13.30% ofconsumers in any way. As a result, deceptive honey commercials lead to consumer abuse and createan environment of distrust of honey. In order to minimize speculation on honey, it is seen necessaryto increase deterrent penalties for businesses that lead to unfair competition.

Bal, tüketiciler tarafından en çok bilinen ve tüketilen arı ürünüdür. Bu nedenle geçmişten günümüze balın temini ve tüketimi üzerine etki eden faktörlerin araştırılması araştırmacıların gündeminde olmuştur. Bu amaçla, anket çalışmamızda televizyon kanalları (reklamları) vasıtasıyla gerçekleştirilen bal satışlarının tüketici nezdindeki etkileri araştırılmıştır. Anket sonuçlarına göre tüketicilerin %87,91’inin televizyondan bal satışları ile ilgili olumsuz, %3,54’ünün olumlu görüşe sahip oldukları, %8,55’inin ise konu ile ilgili herhangi bir fikrinin olmadığı belirlenmiştir. Tüketicilerin %5,83’ünün televizyon reklamlarından bal satın aldığı ve bal satın alma eğiliminde; eğitim, gelir, cinsiyet ve hanelerindeki birey sayısının etkili olduğu tespit edilmiştir. Tarım ve Orman Bakanlığı tarafından sahte veya tağşişli bal satışı yapan şirketlerin teşhir edilmesi ile ilgili olarak, tüketicilerin %54,53’ü bala olan güven konusunda olumlu yönde etkilendiğini, %13,30’u olumsuz yönde etkilendiğini ve %32,17’si ise hiçbir şekilde etkilenmediğini belirtmiştir. Sonuç olarak; aldatıcı bal reklamları tüketici nezdinde istismara yol açmakta ve bala karşı güvensizlik ortamı oluşturmaktadır. Bal üzerindeki spekülasyonları engellemek en aza indirmek adına haksız rekabete yol açan işletmelere caydırıcı cezaların arttırılması elzem görülmektedir.
Televizyon Reklamları İle Gerçekleştirilen Bal Satışlarının Tüketicilerin Satın Alma Davranışları Üzerine Etkileri